Avaliação de impacto do Plano BR-163 Sustentável sobre municípios em sua área de influência no Pará/Brasil - Alves de Araújo, Letícia; Freitas Rodrigues, Diego; Junkes, Janaína A. (Brasiliana: Journal for Brazilian Studies, 2024)
Objective: Evaluate the impact of the Sustainable BR-163 Plan and identify the presence of spatial clusters that explain the territorial dynamics of the micro-regions of influence of the BR-163. Method: An impact assessment was carried out based on the Differences in Differences model, analyzing years before and after its creation. The empirical strategy adopted was based on: a model without matching adjustments; one with weighted inverse probability; and one with the nearest neighbor pairing. Results: It was observed that the estimate of the policy effect is positive and significant in the three models. In the first, there was an increase of 1.234% in the difference in post-policy deforestation in the municipalities in the area of influence of the highway; in the second it rises to 1.426% and stays at 1.335% in the nearest neighbor pairing. It was identified that there was a slowdown in the advance of deforestation, a positive point, however, it is not possible to state that this fact resulted from the implementation of the plan or by other municipal and state policies and incentives. Conclusion: The spatial association analysis carried out showed that the variables Deforestation, Burning Spots and Pasture Area can be discussed at the level of spatial groupings, but do not present similar trends for the entire area of influence of the highway.